Narrative hegemony and its penal techniques in the poetic text in the hadith Yassin Taha Hafez as a model (Journal of the College of Basic Education, 2022)
The modern poetic text has not been subjected to such a massive exposureWorld War II script dominanceThe dominance of the narration at the joints of most of the texts of his poets, until those texts became permissible spacesIn which the narration reaches and wanders, and it seems that the modern poet abandoned lyricism and turned to other approaches Such as romanticism, realism, and symbolism did not prevent the emergence of another form, seeking help this timeyou lyrical waWith the capabilities of the narration to confuse or spread a thick fog that prevents his poetry from being stigmatized by lyricism, especially thatThe phenomenon of poetic narration is entirely a subjective lyrical phenomenon, except for the rare experiences of poets in their textsNarratives such as al-Sayyab, al-Malaikah, Baland, al-Bayati, and those who came to them from the poets or those who came after them, are only evidence ofWhat we say, and from here we can prove the phenomenon of narrative hegemony over the modern poetic text, that hegemony